Seismic microzoning of Guwahati metropolitan area, Assam, India. Issue 142 (March 2021) - Gupta, I.D.; Lee, V.W.; Trifunac, M.D.
Abstract: Seismic microzonation maps for Guwahati metropolitan area are presented based on the Uniform-Hazard-Spectrum (UHS) methodology. UHS method satisfies the performance-based design (PBD) criteria, which are based on two sets of spectral amplitudes, one for which the structure will remain linear, and the other for which it may undergo nonlinear response. The UHS method also considers contributions from large distant earthquakes and includes simultaneously the effects of site geology and of site soils. The maps presented include in a balanced way the effects of near and distant large earthquakes, spatial distribution of seismic activity, the site geology and site soil properties. The results also show that scaling design spectra by peak acceleration to which a standard spectral shape is anchored is not conservative. Highlights: Microzonation maps, which include a description of site geology and site soil. Contribution of large distant earthquakes to long period design spectra. Mapping hazard for earthquakes with different attenuation laws. Application of Uniform Hazard Spectra method to seismic microzonation.